Effective intentions the power of conscious will - Mele, Alfred R., 1951- (Oxford : Oxford University Press, 2009)
Do your intentions have no effect on your actions? Is free will an illusion? Some scientists say yes. Alfred Mele shows that these claims are not justified by the data and that there is weighty evidence of the existence of effective conscious intentions or the power of conscious will.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Will; Consciousness; Intentionalism